2010
DOI: 10.1128/aem.00718-10
|View full text |Cite
|
Sign up to set email alerts
|

Use of Purified Clostridium difficile Spores To Facilitate Evaluation of Health Care Disinfection Regimens

Abstract: Clostridium difficile is a major cause of antibiotic-associated diarrheal disease in many parts of the world. In recent years, distinct genetic variants of C. difficile that cause severe disease and persist within health care settings have emerged. Highly resistant and infectious C. difficile spores are proposed to be the main vectors of environmental persistence and host transmission, so methods to accurately monitor spores and their inactivation are urgently needed. Here we describe simple quantitative metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 35 publications
4
89
1
2
Order By: Relevance
“…We observed that all strains (wild type and mutants) were sensitive to Virkon, hydrogen peroxide, and a temperature of 80°C, in agreement with previous work (38). Spores of all strains were essentially resistant to heat exposure at 65°C, but in some cases (630⌬erm and the cotE::CT1203s and sodA::CT394s strains), counts of survivors were greater than the starting CFU.…”
Section: Figsupporting
confidence: 80%
“…We observed that all strains (wild type and mutants) were sensitive to Virkon, hydrogen peroxide, and a temperature of 80°C, in agreement with previous work (38). Spores of all strains were essentially resistant to heat exposure at 65°C, but in some cases (630⌬erm and the cotE::CT1203s and sodA::CT394s strains), counts of survivors were greater than the starting CFU.…”
Section: Figsupporting
confidence: 80%
“…C. difficile-colonized individuals with a low colonic density of organisms may not participate in the CDI transmission cycle; this is unlikely, however, because the infectious doses for CDIs in animal models are low (15) and C. difficile-colonized patients within hospitals are well documented to be responsible for contamination of hospital rooms and transmission to new patients (16)(17)(18). It is also notable that the majority (67%) of C. difficile-colonized participants who submitted Ͼ1 stool specimen tested negative for C. difficile 30 days after submission of their positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…Spore formation is essential for C. difficile to survive exit from the host and transmit disease because its vegetative cells are exquisitely sensitive to oxygen (8). Furthermore, C. difficile spores are resistant to antibiotics (9), attacks from the host's immune system (10), and disinfectants commonly used in hospital settings due to their metabolic dormancy and intrinsic resistance properties (11)(12)(13)(14). Thus, understanding the mechanisms controlling C. difficile spore germination may have practical applications in the management of C. difficile infections as this knowledge may lead to new methods for preventing spore germination or efficiently promoting it to facilitate killing of the less resistant germinated spores.…”
Section: Importancementioning
confidence: 99%